Does the Number of Victims Matter in Defining Serial Murder? An Analysis of Homicide Behavioral Characteristics in US Cases from 1985–2016 - Vincent, Jolene (Victims & offenders, 2024)
Historically, definitions of serial murder in the academic and professional literature vary, sometimes considerably, based on numbers of victims, offender intent, and presence or absence of a psychological “cooling-off period.” To date, an agreed upon definition remains elusive. This study uses a multinomial regression analysis to examine important homicidal behavioral characteristics of serial killers (N = 1,258) in the US concerning offenders who killed two victims compared to counterparts who murdered three, four or five, and six or more victims, respectively. Important case characteristics between categories are observed and discussed. Findings support definitional recommendations that include a minimum victim threshold of three.